Modelling forest snow processes with a new version of WaSiM. Issue 10 (27th July 2018) - Förster, Kristian; Garvelmann, Jakob; Meißl, Gertraud; Strasser, Ulrich
ABSTRACT: We present a new model extension for the Water balance Simulation Model, WaSiM, which features (i) snow interception and (ii) modified meteorological conditions under coniferous forest canopies, complementing recently developed model extensions for particular mountain hydrological processes. Two study areas in Austria and Germany are considered in this study. To supplement and constrain the modelling experiments with on-site observations, a network of terrestrial time-lapse cameras was set up in one of these catchments. The spatiotemporal patterns of snow depth inside the forest and at the adjacent open field sites were recorded along with snow interception dynamics. Comparison of observed and modelled snow cover and canopy interception indicates that the new version of WaSiM reliably reconstructs the variability of snow accumulation for both the forest and the open field. The Nash-Sutcliffe efficiency computed for selected runoff events in spring increases from −0.68 to 0.71 and 0.21 to 0.87, respectively.